The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jhin.2014.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The Early Mobility Bundle: a simple enhancement of therapy which may reduce incidence of hospital-acquired pneumonia and length of hospital stay

Abstract: The Early Mobility Bundle demonstrates a promising method to reduce the incidence of HAP and to increase activity in medical inpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 21 publications
3
58
0
Order By: Relevance
“…Although only two studies were found, early mobilization interventions appear to reduce HAP incidence [45]. Post-stroke patients in particular could benefit from early mobilization, especially in the 48 h after the ischemic event [43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although only two studies were found, early mobilization interventions appear to reduce HAP incidence [45]. Post-stroke patients in particular could benefit from early mobilization, especially in the 48 h after the ischemic event [43].…”
Section: Resultsmentioning
confidence: 99%
“…A prospective cluster study including 1179 subjects from elderly and respiratory care compared the effect of an early mobility bundle programme in one hospital to usual care in a second one [45]. The primary outcome was incidence of HAP.…”
Section: Measures For Hap Preventionmentioning
confidence: 99%
“…Many early movement initiatives are considered safe and beneficial for patients in adult and pediatric populations . Children and their families admitted to hospital with critical illness, benefit from daily mobility activities and many long‐term functional consequences of hospitalization may be prevented with early and regular mobility, often with the guidance from a physiotherapist .…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of a care bundle to enhance early mobility [17] was associated with a lower risk of HAP (OR 0.39; 95% CI 0.22 to 0.68, p=0.001), although falls rates were non-significantly higher in the early mobility group.…”
mentioning
confidence: 97%